Functional Magnetic Resonance Connectivity in Patients With Temporomadibular Joint Disorders - Festa, Felice; Rotelli, Chiara; Scarano, Antonio; Navarra, Riccardo; Caulo, Massimo; Macrì, Monica (Frontiers in Neurology, 2021)
Abstract Myofascial pain in the masticatory region, generally referred as headache, is a common temporomandibular disorder (TMD) characterized by hypersensitive regions of contracted skeletal muscle fibres. A correct clinical treatment of myofascial pain has the potential to modify the functional activation of cerebral networks associated with pain and unconscious teeth clenching, specifically the pain network (PN) and default mode network (DMN). In this study, research is presented as a case-series of 5 patients with myofascial pain: 3 were diagnosed with intra- and extra-articular disorders, and 2 were diagnosed with only extra-articular disorders. All 5 patients received gnathological therapy consisting of passive splints and biofeedback exercises for tongue-palatal vault coordination. Before and after treatment, patients underwent pain assessments (through measures of visual analogue scales and muscular palpation tests), nuclear magnetic resonance of the temporomandibular joint, and functional nuclear magnetic resonance of the brain. In each patient, temporomandibular joint nuclear magnetic resonance results were similar before and after the gnathological treatment. However, the treatment resulted in a considerable reduction in pain for all patients, according to the visual analogue scales and the palpation test. Furthermore, functional nuclear magnetic resonance of the brain clearly showed a homogeneous modification in cerebral networks associated with pain (i.e., PN and DMN), in all patients. In conclusion, gnathological therapy consisting of passive aligners and biofeedback exercises improved myofascial pain in all 5 patients. Most importantly, this study showed that all 5 patients had a homogeneous functional modification of pain and default mode networks. Using passive splints in combination with jaw exercises may be an effective treatment option for patients with TMD. This research could be a starting point for future investigations and for clinicians who want to approach similar situations.